Multislice Computed Tomography Imaging of Total Anomalous Pulmonary Venous Circulation: Three Rare Case Reports (Ibrahim Cardiac Medical Journal, 2018)
Total anomalous pulmonary venous connection is a rare congenital cardiac anomaly in which the pulmonary veins have no connection with the left atrium and connect directly to the right atrium or to one of the systemic veins. In the diagnosis of total anomalous pulmonary venous connection, the presence and severity of the venous obstruction is important. Computed Tomography (CT) imaging is known to be a useful method for the evaluation of total anomalous pulmonary venous connection. Here we report 3 cases of total anomalous pulmonary venous circulation (TAPVC) where 32 slice CT scan played an important role in pre-operative diagnosis and management. Age of the patients ranged from seven months to sixteen years. Symptoms of the patients’ varied from fatigue, shortness of breath, mild cyanosis and reduced growth for their age. Echocardiography done revealed dilated right cardiac chambers and atrial septal defect (ASD) with suspicion of TAPVC. CT scan was performed and it provided detailed information about intra-cardiac anatomy, pulmonary veins and their confluence, route, drainage and most importantly their distance and relation with the left atrium. It also provided information about coronary sinus and its drainage. This information is very important for surgical mapping and planning.Ibrahim Card Med J 2016; 6 (1&2): 73-77